Synthesis and Structural Characterization of Diiron Ethanedithiolate Complex (μ-SCH2)2Fe2(CO)5(Ph2PNHPy) Relevant to the Active Site of [Fe-Fe]-Hydrogenases - Gao, Wei; Li, Xian (Asian Journal of Chemistry, 2014)
A diiron ethanedithiolate complex (μ-SCH2)2Fe2(CO)5(Ph2PNHPy) (1) has been prepared and characterized by spectroscopy. The title complex was prepared by reaction of [(μ-SCH2)2]Fe2(CO)6 (A) with Ph2PNHPy in the presence of the decarbonylating agent Me3NO·2H2O in acetonitrile at room temperature in 51 % yield. The new complex was characterized by IR, 1H NMR, 31P NMR and 13C NMR spectroscopy.